THE RELATIONSHIP BETWEEN OCCUPATIONAL SAFETY AND HEALTH BEHAVIOR AND WORKPLACE ACCIDENTS IN MICRO, SMALL AND MEDIUM RATTAN BUSINESSES IN GRESIK DISTRICT - Durrotul Hikmah, Nurul Fauziyah; Inayah, Zufra (Universitas Kusuma Husada Surakarta, 2025)
Work accidents are caused by events in the work environment which are certain to harm various parties and even lead to disability and even the most fatal event, namely death. Work accidents in Gresik Regency Rattan MSME's that appear to dominate are due to a lack of knowledge, attitudes, compliance and Personal Protective Equipment. The aim is to find out how the relationship between Occupational Safety and Health behavior and the incidence of work accidents in Rattan Micro, Small, and Medium Enterprises in Gresik Regency. The study was conducted cross-sectionally and classified as quantitative. The total population involved is 278 workers who worked in 16 semi-finished rattan MSME's. The selected participants were randomized (simple random sampling) and Slovin's formula, resulting in a total of 165 workers as respondents. Data collection was conducted through three main methods, namely direct observation, interviews, and questionnaires. The variables used are OHS behavior which includes OHS knowledge, OHS attitude, OHS compliance and the use of personal protective equipment (independent), while the incidence of work accidents (dependent). Data analysis used 2 statistical test methods, both Chi-square and Fisher's exact test. The results of the study concluded several statements, there is a relationship between knowledge and work accidents (p = 0.008), there is a relationship between attitude, compliance with work accidents (p = 0.000), there is a relationship between Personal Protective Equipment and work accidents (p = 0.004). The dominant factor influencing work accidents is the factor of compliance with work instructions (OR 13.993). Suggestions for improvement are that it is hoped that Gresik Regency Rattan MSME 's will impose regular training on work safety procedures to workers in order to increase workers awareness as well as to ensure that PPE is available and used.